Getting to yes : negotiating an agreement without giving in - Fisher, Roger, 1922-2012; Ury, William (London : Random House Business, 2012)
The world's bestselling guide to negotiation. 'Getting To Yes' has been in print for over thirty years, and in that time has helped millions of people secure win-win agreements both at work and in their private lives.
Chapter 1. Don't bargain over positions -- Chapter 2. Separate the people from the problem -- Chapter 3. Focus on interests, not positions -- Chapter 4. Invent options for mutual gain -- Chapter 5. Insist on using objective criteria -- Chapter 6. What if they are more powerful? (Develop your BATNA -- Best alternative to a negotiated agreement) -- Chapter 7. What if they won't play? (Use negotiation jujitsu) -- Chapter 8. What if they use dirty tricks? (Taming the hard bargainer).
Previous edition: 1999.
Includes bibliographical references.
Keywords: Negotiation in business; Leadership; Interpersonal Relations